The effect of rhinovirus on airway inflammation in a murine asthma model - Kim, Eugene; Lee, Huisu; Kim, Hyun Sook; Won, Sulmui; Lee, Eu Kyoung; Kim, Hwan Soo; Bang, Kyongwon; Chun, Yoon Hong; Yoon, Jong-Seo; Kim, Hyun Hee; Kim, Jin Tack; Lee, Joon Sung (Clinical and experimental pediatrics, 2013)
The aim of the present study was to investigate the differences in lower airway inflammatory immune responses, including cellular responses and responses in terms of inflammatory mediators in bronchoalveolar lavage fluid (BALF) and the airway, to rhinovirus (RV) infection on asthma exacerbation by comparing a control and a murine asthma model, with or without RV infection. BALB/c mice were intraperitoneally injected with a crude extract of Dermatophagoides farinae (Df) or phosphate buffered saline (PBS) and were subsequently intranasally treated with a crude extract of Df or PBS. Airway responsiveness and cell infiltration, differential cell counts in BALF, and cytokine and chemokine concentrations in BALF were measured 24 hours after intranasal RV1B infection. RV infection increased the enhanced pause (Penh) in both the Df sensitized and challenged mice (Df mice) and PBS-treated mice (PBS mice) (P<0.05). Airway eosinophil infiltration increased in Df mice after RV infection (P<0.05). The levels of interleukin (IL) 13, tumor necrosis factor alpha, and regulated on activation, normal T cells expressed and secreted (RANTES) increased in response to RV infection in Df mice, but not in PBS mice (P<0.05). The level of IL-10 significantly decreased following RV infection in Df mice (P<0.05). Our findings suggest that the augmented induction of proinflammatory cytokines, Th2 cytokines, and chemokines that mediate an eosinophil response and the decreased induction of regulatory cytokines after RV infection may be important manifestations leading to airway inflammation with eosinophil infiltration and changes in airway responsiveness in the asthma model.